Establiments comercials i fires en la poesia de Pau Puig. - SERRA MILÀ, MARIA-ROSA (Scripta, 2017)
Within Pau Puig's works we can find some twenty pieces related to shops and inns in Barcelona. Most of them refer to small shrines or chapels located there. Pau Puig, compliant with his style, shows an easygoing tone and uses a wide range of collocations and puns when mentioning the commercial activity of each establishment. Puig is much more satyrical about the libertine mores of his time in his work El Sarrabal de la ciudad de Barcelona para el año 1792 (a kind of What's On in Barcelona in 1792). This work is written in Spanish prose and makes fun of the calendars and forecasts. He also shows a list of public holidays, religious processions, parties and fairs that take place in Barcelona througout the year. In some cases the author includes poems in Spanish and Catalan to enlighten the celebrations. This paper will focus on the poems related to fairs.